Edukasi Bahaya Penggunaan Cotton Buds: Upaya Pencegahan Risiko Kesehatan - Setiawan, Salsabila Alifiyah; Imanto, Mukhlis (Medula, 2024)
A common practice in the community is to clean the ears independently to remove earwax that is considered annoying. The act of cleaning the ear canal by using ear cotton aids, actually causes the cerumen to be pushed deeper, which can close the tympanic membrane, causing temporary hearing loss. Cleaning the ear itself is inserting objects into the ear canal with the aim of removing earwax is a practice that has the potential to disrupt the natural cleaning mechanism, and is a risk factor for injury to the ear. Community service activities in the form of counseling “Education on the Dangers of Using Cotton Buds” were carried out on Thursday, January 25, 2024 which took place on the 3rd floor of the Poli Dr. H. Abdul Moeloek Hospital Lampung Province. This activity was attended by 12 audiences who were patients who were checking themselves to the ENT-KL Poly and Poly on the 3rd floor of the Poly Building of Dr. H. Abdul Moeloek Hospital Lampung Province. Pre and Post Tests were conducted as a measuring tool to evaluate the increase in audience knowledge after being given counseling. An increase in percentage was obtained, from 60% in the pretest results and 97% in the post-test results. This counseling activity proved to be effective in increasing community knowledge so it is recommended to be carried out regularly. Lack of knowledge about the dangers of using cotton buds could potentially increase the risk of ear injury. Therefore, it is important to educate the community on the correct way to care for the ears, as well as the dangers of improper use of cotton buds. Through this counseling activity, it is hoped that it can increase public awareness and understanding of the importance of safe and healthy ear care.